Development of Effervescent Granules with Solid Dispersion of Furazolidone - A. O. Elagina; A. V. Beliatskaya; I. I. Krasnyuk (Jr.); I. I. Krasnyuk; O. I. Stepanova; A. N. Vorob'yov; T. V. Fateeva (Разработка и регистрация лекарственных средств)
Introduction. Treatment of infectious and inflammatory diseases demands active substances (AS), characterized by low resistance of microorganisms, high specificity of the mechanism of action and a wide range of antimicrobial activity. Though furazolidone (FZ) – AS meets these criteria, however, practically insolubility in water significantly limits its use. Use of the solid dispersion method (SD) could increase the solubility and dissolution rate of AS with low water solubility. revious studies indicate an increase in the solubility and dissolution rate of FZ in water from SD with polyvinylpyrrolidone-24 000 (PVP-24 000) in a ratio with AS > 6 : 1 by weight. As a result, it becomes possible to introduce SD FZ into the composition of rapidly dissolving effervescent dosage forms, for example, granules for obtaining solutions for external use for the treatment of infectious and inflammatory diseases.Aim. Development of the composition and technology for producing effervescent granules based on solid dispersions of FZ for obtaining a solution for external use.Materials and methods. FZ substance, polyvinylpyrrolidone-24 000 ± 2000 (PVP-24 000 ± 2000), tartaric acid, malic acid, sodium carbonate anhydrous, ethyl alcohol 96 %, purified water. We provided the granules through fluidized bed granulation. The analysis of the obtained granules included the following parameters: description, granule size, loss in mass on drying, disintegration, uniformity of dosage according to GPМ 1.4.1.0004.15 "Granules". Then followed a qualitative and quantitative determination of AS and analysis of the pH of the aqueous solution of the granules. To study the stability and shelf life of the samples of granules, we laid them to the storage in accordance with GPМ 1.10009.15 "Stability and shelf life of drugs".Results and discussion. We developed he composition and technology of FZ effervescent granules for obtaining a solution for external use. Granules are obtained by separate granulation of the main (containing a SD AS) and acid components, followed by mixing in ratios that provide a solution of FZ with a concentration of 0.004 % in water at room temperature. Later we assessed the quality of the obtained compositions and determined, the shelf life (2 years) and storage conditions (in a dry, dark place at a temperature of 25 °C) of the developed compositions of granules.Conclusion. As a result of technological and chemical-pharmaceutical research using the SD method, we developed a new FZ dosage form – effervescent granules, which makes it possible to obtain an aqueous solution with a concentration of FZ 0.004 % in less than 5 minutes without heating. Based on the results of the work, an application was filed with Rospatent No. 2021105988 dated 10.03.2021, "Fast-dissolving dosage form of furazolidone and a method for its production".